Everyday Cognition in Prodromal Huntington Disease - Williams, Janet K. (Neuropsychology, 2014)
OBJECTIVE: Assessment of daily functions affected by cognitive loss in prodromal Huntington disease (HD) is necessary in practice and clinical trials. We evaluated baseline and longitudinal sensitivity of the Everyday Cognition (ECog) scales in prodromal HD and compared self- and companion-ratings. METHOD: Everyday cognition was self-assessed by 850 participants with prodromal HD and 768 companions. We examined internal structure using confirmatory factor analysis (CFA) on baseline data. For longitudinal analysis, we stratified participants into Low, Medium, and High disease progression groups. We examined ECog scores for group differences and participant-and-companion differences using linear mixed effects regression (LMER). Comparison with the Total Functional Capacity (TFC) scale was made. RESULTS: CFA revealed good fit of a 5-factor model having a global factor (total score), and sub factors (subscales) of memory, language, visuospatial perception, and executive function. At study entry, participants and companions in the Medium and High groups reported significantly worsened everyday cognition as well as significant functional decline over time. Losses became more pronounced and participant and companion ratings diverged as individuals progressed. TFC showed significant functional loss over time in the High group but not in the Medium group. CONCLUSIONS: Disease progression is associated with reduced self- and companion-reported everyday cognition in prodromal HD participants who are less than 13 years to estimated motor onset. Our findings suggest companion ratings are more sensitive than participants’ for detecting longitudinal change in daily cognitive function. ECog appears more sensitive to specific functional changes in the prodrome of HD than the TFC.